Identification of the Mtus1 Splice Variant as a Novel Inhibitory Factor Against Cardiac Hypertrophy. Issue 7 (July 2016) - Ito, Shin; Asakura, Masanori; Liao, Yulin; Min, Kyung‐Duk; Takahashi, Ayako; Shindo, Kazuhiro; Yamazaki, Satoru; Tsukamoto, Osamu; Asanuma, Hiroshi; Mogi, Masaki; Horiuchi, Masatsugu; Asano, Yoshihiro; et al.
Abstract : Background: In cardiac hypertrophy and failure, there is a widespread alteration in mRNA splicing, but the role of splice variants in cardiac hypertrophy has not yet been fully elucidated. In this study, we used an exon array to identify novel splice variants associated with cardiac hypertrophy. Methods and Results: We performed genome‐wide exon array analysis and developed a splicing profile in murine hearts with hypertrophy induced by transverse aortic constriction for 8 weeks. Following global analysis of splice variants using the Mouse Exon 1.0 ST Array, we identified 46 spliced genes and narrowed our focus to 1 gene, mitochondrial tumor suppressor 1 ( Mtus1 ), whose splice variants were registered in the NCBI RefSeq database. Notably, one of the splice variants Mtus1A was specifically upregulated, although the total expression of the Mtus1 gene remained unchanged. We showed that Mtus1A was localized in the mitochondria, and its expression level increased with the degree of cardiac hypertrophy. In cultured cardiomyocytes, Mtus1A overexpression reduced phenylephrine‐induced reactive oxygen species production and consequent ERK phosphorylation, resulting in a decrease in both cell size and protein synthesis. In vivo, cardiac‐specific Mtus1A transgenic mice showed left ventricle wall thinning and a reduced hypertrophic response to pressure overload and phenylephrine treatment. Conclusions: We found that Mtus1 is specifically spliced in hypertrophic hearts and that the Mtus1A variant has an inhibitory effect on cardiac hypertrophy. Mtus1A is, therefore, a possible diagnostic and therapeutic target for cardiac hypertrophy and failure.